EXPLORING TYPES OF I’LAL AND EFFECTIVE LEARNING STRATEGIES IN ARABIC LANGUAGE TEACHING - Pertiwi, Resta Okta; Sagala, Rumadani; Erlina, Erlina; Koderi, Koderi; Sufian, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the types of i’lal in Ilmu Sharaf and explore effective learning strategies to enhance students’ understanding of Arabic morphological concepts. A qualitative approach with a descriptive linguistic study design was employed, involving the analysis of classical Arabic morphology texts and classroom observations at Pondok Pesantren Al Hidayah Keputran. The findings indicate that i’lal consists of four main types: i’lal with qalb (substitution of huruf illat), i’lal with taskin (formation of sukun), i’lal with hadzf (elision of huruf illat), and i’lal with naql harakat (transposition of vowel movements on huruf illat). The study confirms that i’lal with qalb is the most dominant form in classical Arabic texts, particularly in ajwaf verbs. Additionally, the research highlights key challenges in learning i’lal, including insufficient comprehension of sharaf rules, the dominance of rote memorization without in-depth analysis, and the limited use of interactive learning media. To address these challenges, the inductive and tamrinan methods were found to be more effective than traditional memorization-based approaches. This study suggests that i’lal instruction should adopt a combined method, incorporating example-driven learning, word analysis exercises, and digital learning tools to enhance students' understanding of morphological transformations in Arabic.